The concept of accessibility in public transportation services - Saravanan Sundara Sakaran; Harifah Mohd Noor (2020)
In the world of modernization and globalization, accessibility plays an important role in daily social activities. Public transportation also plays an important role in the movement of people from one place to another. However, the concept of accessibility has different meanings based on statements made by previous scholars based on the geographical position of a particular space. Therefore, the objective of this paper is to look at the concept of accessibility in general and the mode of public transportation services is to be looked into in particular. This study uses secondary sources to explain the concept of accessibility in general and the mode of public transportation services specifically. Among the secondary sources used in this study are journal articles, books, theses and reports. Therefore, content analysis was implemented in this study to unravel the concept of public transport accessibility in depth. The results of this study found that the concept of public transportation accessibility is influenced by several aspects such as social, economy and politic. The implications of this study can be divided into two parts namely; the implications of the body of knowledge and the implication on the view of practical points in order to contribute help to policy planners and decision-makers to better understand the concept of public transportation accessibility so that the future formulation of policies could be enacted with taking the indicator of public transportation accessibility into account.